Jalur Kritis Pada Manajemen Proyek untuk Aplikasi Website Sekolah - Juliana, Juliana; Driyani, Dewi; Khotijah, Siti (Universitas Islam Syekh Yusuf, 2021)
One of the benefits of project management in making school website applications is finding the best time to create projects, by looking for critical paths in project management. The analysis will be more specific in finding the critical path, comparing and finding the best time in making school website application projects, job scheduling, network diagrams, and time management. The data collection used in this study is primary data, namely conducting interviews with school website application users, namely teachers and school principals. In finding the critical path by making a Gantt Chart, WBS (Work Breakdown Structure), Critical Path Method (CPM). The purpose of finding a critical path in project management is to reduce the risk of time failure in school website application projects. The result of this research is to make the project on time and not experience delays.